PERENCANAAN SISTEM PENYALUR PETIR PADA GEDUNG - A UNIVERSITAS MPU TANTULAR CIPINANG - Widiarto, Indra; Sinambela, Pahala; Sinambela, Rismen (Bhinneka Multidisiplin Journal, 2024)
Mpu Tantular University is one of the leading Universities in Indonesia and has three buildings to support learing/teaching activities. Bulding-A Mpu Tantular University has 8 floors. As a vital place and has a potential for lightning strikes, because it is classified as a building with a risk of lightning strikes, Building-A need to be calculated and planned for an external lightning conductor, so that the electronic equipment inside is safe if there is a lightning strike. In determining whether or not a lightning protectionsystem is necessary, a comparative study should be carried out using the reference to the Indonesian National Standart SNI 03-7015-2004 concerning Lightning Protetion System in Buildings. The design of this lightning protection system uses the Rolling Sphere method on the Air Termination System and Multiple Rod on Earthing Termination System, so that the condition of Building-A is safe and in accordance with applicable regulation in building planing